2020
DOI: 10.1021/acs.iecr.0c01741
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Optimality for Separation System Synthesis Using Rigorous Modeling, Stochastic Optimization, and Column Stacking

Abstract: Alternatives for the separation of three-component zeotropic mixtures are compared using simulation optimization with the total annual cost as the objective function. Conventional two-column sequences with and without column stacking are compared with three types of dividing-wall columns (DWCs). All processes are modeled with a rigorous process simulator and optimized using simulated annealing. The results are represented using ternary maps and used to regress parameters of a model that predicts the relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…There is no built-in models for DWCs in Aspen Plus, therefore multiple Radfrac blocks are used to represent a single DWC, as shown in Figures S1−S3. 17 Abbreviations for all configurations considered in this work are shown in Table 1. All distillation columns are rigorously simulated using the Radfrac model in Aspen Plus V12.…”
Section: Distillation Configurationsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is no built-in models for DWCs in Aspen Plus, therefore multiple Radfrac blocks are used to represent a single DWC, as shown in Figures S1−S3. 17 Abbreviations for all configurations considered in this work are shown in Table 1. All distillation columns are rigorously simulated using the Radfrac model in Aspen Plus V12.…”
Section: Distillation Configurationsmentioning
confidence: 99%
“…Although DWCM can reduce TAC by 1.7% compared with the optimal unstacked conventional sequence (DS), CISH can reduce TAC by 13.1% compared with the optimal unstacked conventional sequence (DS), which is significantly greater than DWCM. Lin et al 17 and Tang and Ward 22 found that DWCU is preferable for mixtures with ESI (ease of separation index 31 ) larger than one, DWCL is preferable for mixtures with ESI less than one, and DWCM is preferable for mixtures with ESI around one. For mixture MCM (ESI < 1) studied in this work, the rank order of TAC for DWCs is DWCU > DWCL > DWCM.…”
Section: Unstacked and Stacked Complex Sequencesmentioning
confidence: 99%
See 3 more Smart Citations